Study on failure of a tie rod for two-wheeler automotive gear mechanism; [Étude sur la défaillance d’une biellette pour mécanisme d’engrenage automobile à deux roues] - Verma P.; Vaishnav D.; Nandan A.; Verma D.; Raghupathy R.; Telikepalli K.P.; Kumar A. (My University, 2025)
Failure studies of gear shifter tie rod assemblies are crucial for enhancing automotive system reliability and safety. The origin of a tie rod assembly failure is analysed through chemical, mechanical, microstructural, and fractographic analysis in this paper. Optical imaging reveals the microstructure of heat-treated steel, while fractography shows fatigue striations, indicating a progressive fracture. According to the analysis, the penultimate thread likely had a fracture due to the minimal radial space between the external thread and the head. The macroscopic and microscopic characteristics indicate failure from reverse bending under cyclic loading. A crack propagation and ultimate fracture mechanism has been proposed to provide a better understanding of tie rod thread part failures. The importance of factors like fatigue, reverse bending, corrosion, misalignment, and material properties in tie rod failures is highlighted in this study. © 2024 Matter Motor Works Pvt. Ltd.